1996
DOI: 10.1046/j.1365-2362.1996.95240.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects of endotoxins and bile acids in vivo in the rat

Abstract: Cell-mediated immunity is impaired during cholestasis. The aim of this study was to evaluate in vivo the effects on this immune defect of high serum levels of endotoxin and bile acids. Heterotopic cardiac allotransplantations were performed in the DA/Lewis rat combination. Cholestasis, induced by ligation/section of the common bile duct, was responsible for a significant delay in the rejection time (16 +/- 0.5 vs. 7.1 +/- 0.4 days in controls, P < 0.01). Elimination of Gram-negative intestinal bacteria from ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(36 reference statements)
1
7
0
3
Order By: Relevance
“…This finding was highly suggestive that bile acids are able to hold bacterial components back in the intestine. Indeed, application of chenodeoxycholic acid to rats in this study was still associated with significantly reduced plasma LPS levels (12). Because elevated levels of LPS are present in patients with CHF (10), the improvement in post-ischemic blood flow observed in our study may be due to the formation of mixed micelles containing UDCA around LPS.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…This finding was highly suggestive that bile acids are able to hold bacterial components back in the intestine. Indeed, application of chenodeoxycholic acid to rats in this study was still associated with significantly reduced plasma LPS levels (12). Because elevated levels of LPS are present in patients with CHF (10), the improvement in post-ischemic blood flow observed in our study may be due to the formation of mixed micelles containing UDCA around LPS.…”
Section: Discussionsupporting
confidence: 47%
“…This is in line with our findings because leukocyte counts decreased with UDCA treatment compared with placebo. An elegant study was presented by Aouad et al (12), who showed that ligation of the common bile duct in Lewis rats yielded significantly elevated levels of LPS in the bloodstream compared with control animals. This finding was highly suggestive that bile acids are able to hold bacterial components back in the intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced immune system function and an impaired inflammatory response are key factors in the development of gut-derived infections in obstructive jaundice [25, 29, 30, 31, 32, 33, 34]. Inflammatory and immunological effects of obstructive jaundice contribute to the development of bacterial translocation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Since most of these data suggested that PGM-Zn is an immunostimulator which shares some properties with the lipopolysaccharide (LPS), but has a different mode of action on lymphatic cells, we speculate that there is the possibility that PGM-Zn has, during jaundice, interfered with some LPS-induced pathways. Namely, in cholestatic jaundice in plasma toxic factors like bilirubin, bile acids, endotoxin, α 2 -globulin and abnormal lipoproteins [11]accumulate, which alter Kupffer cell function [17], interfere with the early events at the T cell recognition stage [18]and impair the cell-mediated immunity [19]. This eventually leads to gut barrier failure, systemic endotoxemia and translocation of bacteria and endotoxin to the liver [20], as well as to release of large quantities of mainly proinflammatory cytokines (TNF-α, IL-1, IL-6) from various host cells [21].…”
Section: Discussionmentioning
confidence: 99%